Pathophysiology of Physical Exercise in Kidney Patients: Unveiling New Players - The Role of Myokines - Daniela Picciotto; Lucia Macciò; Daniela Verzola; Federica Baciga; Claudia Momentè; Elisa Russo; Francesca Viazzi; Yuri Battaglia; Pasquale Esposito (Karger Publishers, 2024)
Background: Chronic kidney disease (CKD) is a progressive systemic condition characterized by numerous complications. Among these, alterations in skeletal muscle physiology, such as sarcopenia, are particularly significant, as they are associated with poor outcomes and reduced quality of life. Summary: Various interventions, including pharmacological approaches and lifestyle modifications have been investigated to slow CKD progression and prevent or treat its complications. Physical exercise, in particular, has emerged as a promising intervention with multiple beneficial effects. These include improvements in physical functioning, increased muscle mass, modulation of metabolic abnormalities, and reduced cardiovascular risk. However, the pathophysiology of physical exercise in patients with kidney disease is complex and remains only partially understood. A crucial advancement in understanding this phenomenon has been the identification of myokines - molecules expressed and released by skeletal muscle in response to physical activity. These myokines can exert both paracrine and systemic effects, influencing not only skeletal muscle physiology but also other processes such as energy metabolism and lipid regulation. Key Messages: The interplay among skeletal muscle, physical activity, and myokines may act as a pivotal regulator in various physiological processes, including aging, as well as in pathological conditions like cachexia and sarcopenia, frequently observed in CKD patients at different stages, including patients on dialysis. Despite the potential importance of this relationship, only a limited number of studies have explored the relationship between exercise and myokine, and the effect of this interaction on experimental models or individuals with kidney disease. In the following sections, we review and discuss this topic.